A bio-based intumescent flame retardant with biomolecules functionalized ammonium polyphosphate enables polylactic acid with excellent flame retardancy. (15th August 2022) - Fang, Quan; Zhan, Yuanyuan; Chen, Xu; Wu, Rongkai; Zhang, Weijia; Wang, Yu; Wu, Xujuan; He, Yunlong; Zhou, Juanjuan; Yuan, Bihe
Graphical abstract: Highlights: A core–shell flame retardant was prepared via the simple ionic interactions. AG as biomass material was firstly applied in intumescent flame-retardant system. The synergistic effect of APP@CS@ATMP and AG in flame-retardant PLA was explored. PLA/APP@CS@ATMP/AG showed excellent flame-retardant and anti-dripping properties. Abstract: A bio-based intumescent flame retardant (IFR) was designed and synthesized by employing a simple and environment-friendly strategy. Via electrostatic interaction, chitosan (CS) and amino trimethylphosphonic acid (ATMP) as organic shells are deposited on the inorganic core of ammonium polyphosphate (APP) to form the core–shell flame retardant (APP@CS@ATMP). Then, agar (AG) is used as a charring agent candidate that combines with APP@CS@ATMP to fabricate a bio-based IFR. The application of APP@CS@ATMP and AG in polylactic acid (PLA) is effective in improving its flame retardancy and anti-dripping properties. The PLA composite including 20 wt% APP@CS@ATMP/AG (APP@CS@ATMP:AG = 3:1) can achieve the optimal flame-retardant effect and a UL-94 V-0 rating with a slight melt-dripping phenomenon. Furthermore, the peak heat release rate and total heat release significantly decrease in the cone calorimetric tests contrasted with those of pure PLA. The flame-retardant mechanism of APP@CS@ATMP/AG is revealed by analyzing the pyrolysis gaseous products during the thermal decomposition and the morphology and structure of char residues. This work provides a facile and sustainable route to construct bio-based polymer composites with excellent fire-safety properties.